Identification of antimalarial compounds directed against falcilysin and their biochemical and structural validation - Lin, Jianqing (Nanyang Technological University, 2025)
Malaria is a widespread infectious disease in tropical and subtropical countries, causing approximately half a million deaths worldwide annually. Emergence of drug-resistant strains has led to a decline in the efficacy of existing drugs, making development of new antimalarial drugs a pressing need. Falcilysin from the malaria parasite is a M16C zinc metallopeptidase in the hemoglobin degradation pathway, which is crucial for parasite growth, and the knockout of falcilysin gene is lethal to malaria, making falcilysin an attractive drug target. Using mass spectrometry-based cellular thermal shift assay (MS-CETSA), falcilysin has been indicated as a possible target of several antimalarial compounds, namely chloroquine, mefloquine, MK-4815, MMV000848, and MMV665806. However, confirmation of the possible falcilysin-compound interactions is crucial due to the common false-positive problem of MS-CETSA. To validate the interactions, isothermal titration calorimetry was first employed to confirm the binding of falcilysin to the compounds. Next, falcilysin enzymatic assay showed that the compounds inhibited falcilysin in a dose-dependent manner. Furthermore, complex structures of falcilysin with each of the compounds were unraveled by X-ray crystallography, revealing a common binding pocket for the compounds. Interestingly, the pocket is 24 Å away from the active site of falcilysin, indicating that the compounds are unlikely compete with falcilysin’s peptide substrates for binding. Indeed, in the co-crystal structures of falcilysin and its peptide substrates, the pocket does not assist in substrate binding, suggesting allosteric inhibition by the compounds. Consistently, it was observed that MK-4815, the most potent inhibitor among the compounds, shifts the equilibrium of falcilysin open/closed conformations in cryo-EM: falcilysin prefers an open conformation in the absence of MK-4815, and a closed conformation in the presence of MK-4815. Subsequent structure analysis uncovered an important helix that mediates the transition between the open and closed conformations of falcilysin. This helix is located right next to the compound binding pocket, and thus binding of MK-4815 restricts the movement of the helix in a way that favors the closed conformation. As a result, this would reduce the number of open falcilysin available for substrate binding, which is the first step of the catalytic cycle, thus inhibiting the protease activity of falcilysin. Taken together, this study validated the interactions between falcilysin and several antimalarial compounds with detailed structural insights of the allosteric inhibition, providing fundamental knowledge for designing and optimizing novel antimalarial drugs targeting falcilysin.